1998
DOI: 10.1016/s0014-5793(98)00922-3
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acids regulate the uncoupling protein and alternative oxidase activities in plant mitochondria

Abstract: Two energy-dissipating systems, an alternative oxidase and an uncoupling protein, are known to exist in plant mitochondria. In tomato fruit mitochondria linoleic acid, a substrate for the uncoupling protein, inhibited the alternative oxidase-sustained respiration and decreased the ADPIO ratio to the same value regardless of the level of alternative oxidase activity. Experiments with varying concentrations of linoleic acid have shown that inhibition of the alternative oxidase is more sensitive to the linoleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 21 publications
3
60
0
2
Order By: Relevance
“…They also show that AOX and PUMP never seem to work simultaneously at least at their maximal activity, and it is likely that when PUMP reaches high activity AOX is already fully switched off (16). addition of KCN and terminated by BHAM.…”
Section: Aox and Pump Activity During Tomato Fruit Post-harvest Ripeningmentioning
confidence: 98%
See 1 more Smart Citation
“…They also show that AOX and PUMP never seem to work simultaneously at least at their maximal activity, and it is likely that when PUMP reaches high activity AOX is already fully switched off (16). addition of KCN and terminated by BHAM.…”
Section: Aox and Pump Activity During Tomato Fruit Post-harvest Ripeningmentioning
confidence: 98%
“…Since the common final effect of the AOX and PUMP activities is a decrease in ATP synthesis efficiency, it can be quantified by ADP/O ratio measurements (16 ADP/O is measured during an ADP pulse (0.17 mM) with succinate (10 mM) plus rotenone as oxidizable substrate. O is the total amount of oxygen consumed during state 3 respiration.…”
Section: Aox-pump Connectionmentioning
confidence: 99%
“…brown adipose tissue), where they act as uncouplers of the mitochondrial electron transport chain, allowing energy derived from lipids to be used for heat generation instead of ATP production (Knutson, 1974;Klingenberg and Winkler, 1985). Furthermore, a number of studies have reported that the AOX and UCP co-occur in plant tissues (Sluse et al, 1998;Considine et al, 2001;Ito and Seymour, 2005). UCP may short-circuit protons that could be transferred before the AOX, accounting for the complete conversion of energy entering the electron transport chain to heat with no ATP production (Seymour et al, 1983;Lamprecht et al, 1998).…”
mentioning
confidence: 99%
“…Although UCP is equally expressed in both thermogenic and nonthermogenic tissues in dead-horse arum (Helicodiceros muscivorus; Ito et al, 2003), it may have a thermogenic function in mitochondria with high AOX activity. However, the free fatty acids that stimulate UCP activity appear to inhibit the AOX, thus it is unlikely that both will reach maximal activity simultaneously (Sluse et al, 1998). The involvement of AOX and UCP appears to depend on the substrate catabolized.…”
mentioning
confidence: 99%
“…The presence of two dissipative pathways in plants is curious, and raises questions regarding the regulation of these pathways. Although the contribution of each pathway under different conditions of plant thermogenesis has not been well established, it now seems clear that these pathways do not operate simultaneously (15).…”
Section: Thermogenesismentioning
confidence: 99%